Sea School U.S. Funds May Double - Vallejo Times-Herald (Vallejo Times-Herald)
Federal appropriations for the four State Maritime Academies, including the California Maritime Academy at Vallejo, will almost double this year, if the amount recommended by President Eisenhower in his Budget is approved by Congress.